Dynamics of Building Agreement in the Mediation Process - Lubis, Fauziah; Aulia, Najri; Habiba, Nur Fitria; Al Husaini, Muhammad Rifqi; Syahdan, Abdul; Harahap, Muhammad Ikbal (Fox Justi : Jurnal Ilmu Hukum, 2025)
The background of this study is based on the fact that mediation as a non-litigation dispute resolution mechanism is increasingly relevant and needed in the modern legal system. Mediation offers a more participatory, flexible, and deliberation-oriented approach and restorative justice. Debt default cases are common examples that often arise in society, where emotional and social relationships between parties are often disrupted due to legal disputes. This study uses a qualitative method with an empirical legal approach and case studies. Data were obtained through interviews, observations, and reviews of legal documents and academic literature. The analysis was carried out using the Miles and Huberman interactive model to understand the dynamics of communication and negotiation in the mediation process. This study aims to analyze the effectiveness of mediation in resolving default disputes on debt agreements, and to identify factors that influence the success or failure of the process. The problem raised is the high dependence of society on litigation which often results in a long process, high costs, and rifts in social relations between the disputing parties. The results of the study indicate that mediation is effective in reducing conflict escalation and producing a legally binding peace agreement through a peace deed. Key success factors include the competence of the mediator, the openness of the parties, and an empathetic communicative approach. Despite obstacles such as ego, the presence of rigid legal counsel, and technical obstacles, mediation remains a viable peaceful solution and is in line with responsive legal reform.